What Drive Industrial Development in Low-Income Economies? Role of Foreign Direct Investment in Chinese Manufcturing - Zhang, Kevin (Archives of Business Research, 2022)
Industrial development (ID) or Industrialization is a must for low-income economies to become developed countries. How does foreign direct investment (FDI) affect ID? This paper aims to answer the question with evidence from a panel dataset of Chinese manufacturing at regional levels in 1990-2020. ID is measured by industrial capacity and industrial technology in both domestic and global markets. Estimate results suggest that (a) FDI fuels China’s industrialization; (b) FDI promotes ID through raising industrial capacity and technology; (c) The positive effects of FDI on seems to be larger on industrial capacity than technology, and larger on exports than domestic markets; and (d) gains from FDI depend significantly on China’s FDI absorptive capacity in terms of infrastructure, human capital, and R&D.